2017
DOI: 10.3802/jgo.2017.28.e76
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of guideline introduction on clinical practice and outcome in patients with endometrial cancer in Japan: a project of the Japan Society of Gynecologic Oncology (JSGO) guideline evaluation committee

Abstract: ObjectiveThe Japan Society of Gynecologic Oncology (JSGO) published the first practice guideline for endometrial cancer in 2006. The JSGO guideline evaluation committee assessed the effect of this guideline introduction on clinical practice and patient outcome using data provided by the Japan Society of Obstetrics and Gynecology (JSOG) cancer registration system.MethodsData of patients with endometrial cancer registered between 2000 and 2012 were analyzed, and epidemiological and clinical trends were assessed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…The results of our study support the findings of the SEPAL study. Because chemotherapy is used in most cases in Japan as an adjuvant treatment [ 1 , 2 , 10 ], the results may differ from those reported in Europe and the United States, where adjuvant radiation therapy is administered [ 11 , 12 ]. The control of pelvic lesions by adjuvant radiation therapy was replaced by regional LN dissection, and further control of systemic lesions by chemotherapy may lead to a prolonged prognosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study support the findings of the SEPAL study. Because chemotherapy is used in most cases in Japan as an adjuvant treatment [ 1 , 2 , 10 ], the results may differ from those reported in Europe and the United States, where adjuvant radiation therapy is administered [ 11 , 12 ]. The control of pelvic lesions by adjuvant radiation therapy was replaced by regional LN dissection, and further control of systemic lesions by chemotherapy may lead to a prolonged prognosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatments for endometrial cancer include total hysterectomy, bilateral salpingooophorectomy, and regional lymphadenectomy. In Japan, regional lymphadenectomy is performed in approximately 60–70% of patients with endometrial cancer [ 2 ]; of these, only a few cases have lymph node (LN) metastasis. Regional LN metastasis is one of the most important prognostic factors in endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer (EC) is the most common gynecologic malignancies in women, and the patients number is increasing year by year. 1,2 Although surgery is the primary therapeutic strategy for EC patients in recent years, its effectiveness is generally unsatisfactory. 3 Up to now, the etiology and pathogenesis of EC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…13 Therefore, among various adjuvant treatments, the use of adjuvant CT significantly increased from 2000 to 2012. 10,11 Therefore, the recurrence patterns, sites, treatments, and prognoses of patients who undergo CT are likely to differ from those of patients involved in previous studies that mostly reported recurrence after radiation. In the present study, we retrospectively summarized the clinicopathological features of patients with EC that recurred after complete remission with primary treatment at 3 large hospitals and revealed the recurrence patterns, treatments, and prognoses for recent REC patients in Japan.…”
mentioning
confidence: 98%
“…The greatest change was that chemotherapy (CT) has become more widely used than RT as an adjuvant treatment after primary surgery. 10,11 In 2008, Susumu et al reported the results of a prospective randomized study comparing CT and RT as the postoperative treatment conducted in Japan (JGOG2033). 12 Although there were no significant differences in overall survival (OS) and progression-free survival (PFS) between the adjuvant CT group and adjuvant RT group in total, both OS and PFS of the CT group were significantly better than those of the RT group in patients with high-intermediate risk.…”
mentioning
confidence: 99%